The end of the soul : scientific modernity, atheism, and anthropology in France - Hecht, Jennifer Michael, 1965- (Columbia University Press, 2003)
On October 19, 1876 a group of leading French citizens, both men and women included, joined together to form an unusual group, The Society of Mutual Autopsy, with the aim of proving that souls do not exist. The idea was that, after death, they would dissect one another and (hopefully) show a direct relationship between brain shapes and sizes and the character, abilities and intelligence of individuals. This strange scientific pact, and indeed what we have come to think of as anthropology, which the group's members helped to develop, had its genesis in aggressive, evangelical atheism.